Discards, hooking, and post-release mortality of porbeagle ( Lamna nasus ), shortfin mako ( Isurus oxyrinchus ), and blue shark ( Prionace glauca ) in the Canadian pelagic longline fishery. (8th December 2015) - Campana, Steven E.; Joyce, Warren; Fowler, Mark; Showell, Mark
Abstract: Global discards of sharks greatly exceed reported landings, yet there are few estimates of mortality after release. Based on more than 21 000 fisheries observer records and the results of 109 popup satellite archival tags, all sources of fishing-induced mortality (harvest, capture, and post-release) were estimated for blue sharks ( Prionace glauca ), shortfin mako ( Isurus oxyrinchus ), and porbeagle ( Lamna nasus ) in the Canadian pelagic longline fishery between 2010 and 2014. Hooking mortality ranged from 15 to 44%, with porbeagles and makos experiencing much greater mortality than blue sharks. The post-release mortality rate varied between 10 and 31%, with porbeagle and mako again having the highest mortality rate. Overall, about one-half of the hooked porbeagles and makos died during or after fishing, with most of the post-release mortality occurring within 2 d of release. Landed catch accounted for less mortality in porbeagle and blue sharks than did the combination of hooking and post-release mortality. These results indicate that the conservation benefits of mandatory release regulations for pelagic longline gear are not nearly as great as is now assumed.